A non-human primate derived anti-P-selectin glycoprotein ligand-1 antibody curtails acute pancreatitis by alleviating the inflammatory responses - Yuhan Li; Xiangqing Ding; Xianxian Wu; Longfei Ding; Yuhui Yang; Xiaoliang Jiang; Xing Liu; Xu Zhang; Jianrong Su; Jianqing Xu; Zhiwei Yang (Elsevier, 2023)
Acute pancreatitis (AP) is a devastating disease characterized by an inflammatory disorder of the pancreas. P-selectin glycoprotein ligand-1 (PSGL-1) plays a crucial role in the initial steps of the adhesive at process to inflammatory sites, blockade of PSGL-1 might confer potent anti-inflammatory effects. In this study, we generated two non-human primate derived monoclonal antibodies capable of efficiently targeting human PSGL-1, RH001-6 and RH001-22, which were screened from immunized rhesus macaques. We found that RH001-6, can effectively block the binding of P-selectin to PSGL-1, and abolish the adhesion of leukocytes to endothelial cells in vitro. In vivo, we verified that RH001-6 relieved inflammatory responses and pancreatic injury in both caerulein and l-arginine induced AP models. We also evaluated the safety profile after RH001-6 treatment in mice, and verified that RH001-6 did not cause any significant pathological damages in vivo. Taken together, we developed a novel non-human primate derived PSGL-1 blocking antibody with high-specificity, named RH001-6, which can interrupt the binding of PSGL-1 and P-selectin and attenuate inflammatory responses during AP. Therefore, RH001-6 is highly potential to be further developed into therapeutics against acute inflammatory diseases, such as AP.